Experimental research methods in orthopedics and trauma - Simpson, A. Hamish R. W.; Augat, Peter (Thieme Publishers, 2015)
From bioinformatics to nanotechnology, advances in basic research ultimately drive advances in clinical care. This book provides a comprehensive summary of all current research methodologies for translational and pre-clinical studies in biomechanics and orthopedic trauma surgery. With this roadmap at hand, specialists and trainees will have the tools to conduct high-quality experimental research in any area of musculoskeletal science, with a solid understanding of how the findings can be applied in patient care. Special Features: Utilizes the principles and methodology of modern, evidence-based